2017
DOI: 10.3892/etm.2017.4669
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed eNOS upregulates SIRT1 expression and protects mouse pancreatic β cells from apoptosis

Abstract: Abstract. Loss of sirtuin 1 (SIRT1) activity may be associated with metabolic diseases, including diabetes. The aim of the present study was to investigate the potential effects of overexpressed endothelial nitric oxide synthase (eNOS) on cell proliferation and apoptosis with SIRT1 activation in the Min6 mouse pancreatic β cell line. A pcDNA3.0-eNOS plasmid was constructed and transfected into Min6 cells for 24 h prior to harvesting. eNOS expression was validated and SIRT1 expression was detected following pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In cultured adipocyte, the SIRT1 expression is enhanced by treatments of NO donors and cGMP analogs (Nisoli et al, 2005). SIRT1 expression is also upregulated by overexpression of eNOS in the cultured mouse pancreatic β-cell line Min6 (Hu et al, 2017). These indicate the importance of eNOS-derived NO as a regulator of SIRT1 expression.…”
Section: Interplay Between Sirt1 and Enos In Regulating Endothelial Fmentioning
confidence: 99%
“…In cultured adipocyte, the SIRT1 expression is enhanced by treatments of NO donors and cGMP analogs (Nisoli et al, 2005). SIRT1 expression is also upregulated by overexpression of eNOS in the cultured mouse pancreatic β-cell line Min6 (Hu et al, 2017). These indicate the importance of eNOS-derived NO as a regulator of SIRT1 expression.…”
Section: Interplay Between Sirt1 and Enos In Regulating Endothelial Fmentioning
confidence: 99%
“…Sirtuin 1 (SIRT1), a NAD + -dependent class III histone deacetylase, expresses in all cell types. It targets a wide range of transcription factors and consequently, is involved in many physiological and pathological processes as diverse as energy metabolism and myogenesis (Michan and Sinclair, 2007), oxidation-stress (Lee et al, 2018), inflammation (Velagapudi et al, 2017), and apoptosis (Hu T. et al, 2017). Recent studies (Potente et al, 2007; Ota et al, 2010) have demonstrated that SIRT1 is highly expressed in the vasculature during blood vessel growth and regulate the angiogenic activity of endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…24 At present, the release of inammatory factors promotes the apoptosis of pancreatic cells, and the reduction in the apoptosis of pancreatic cells aer AP has become one of the current research hotspots in many pathogenesis analyses of AP. 25,26 The selection of animal species and the method of model preparation play important roles in this type of research. A druginduced AP rat model is superior to a mouse model in terms of stability and the degree of pancreatic lesion homogeneity, and rats are also more convenient when it comes to monitoring hemodynamics and organ function.…”
Section: Discussionmentioning
confidence: 99%